APAKAH MODEL EARTHCOMM DAN GAYA BELAJAR DAPAT MEMPENGARUHI KEMAMPUAN BERPIKIR SPASIAL SISWA SMA? - Muhammad Aliman; Dahri Hi Halek; Syahril Lukman; Silvia Marni; Darling Surya Alnursa (JAMBURA GEO EDUCATION JOURNAL, 2022)
Developing spatial thinking in students remains a challenge for many geography teachers in Indonesia. This study examined the process of developing spatial thinking skills in learning styles. Therefore, a relevant learning model is required for developing spatial thinking skills. This research aimed to determine: 1) the effect of earthcomm learning on spatial thinking skills, 2) the effect of learning styles on spatial thinking skills, and 3) the relationship of earthcomm learning and learning styles on spatial thinking skills. The study used a quasi-experimental design with a non-equivalent control pretest-posttest. The data were obtained using a questionnaire to test learning style and spatial thinking ability that had been validated and assessed for normality and reliability. The research population were first-grade students (grade X) in SMAN 15 Padang, West Sumatra. The research sample consists of students from Social Class 2 (X IPS 2) as the control group and students from Social Class 3 (X IPS 3) as the experimental group. The research data were analyzed using the ANOVA technique from the SPSS 25 for Windows. The findings indicated that: 1) earthcomm learning has an effect on spatial thinking skills, 2) learning style has no significant effect on spatial thinking skills, and 3) there is no interaction between earthcomm learning and learning style on spatial thinking skills. This study provided a comprehensive discussion of the research findings.